Ethnobotany, phytochemistry and pharmacology of Biophytum sensitivum DC - Bharati, Abinash C.; Sahu, Alakh N. (Pharmacognosy Reviews, 2012)
Medicinal plants are widely being used by the traditional medical practitioners for curing various diseases in their day-to-day practice. Biophytum sensitivum DC (Oxalidaceae) is used as a traditional folk medicine in ailments such as inflammation, arthritis, wounds, tumors and burns, gonorrhea, stomach ache, asthma, cough, degenerative joint disease, urinary calculi, diabetes, snake bite, amenorrhea and dysmenorrhea. It is a small, flowering, annual herb with sensitive leaves. It grows throughout tropical Africa and Asia, especially in Philippines and the hotter parts of India and Nepal. Phytochemical studies have shown that the major pharmacologically active constituents are amentoflavone and a polysaccharide fraction, BP100 III. Recent pharmacological study shows that it has antioxidant, immunomodulatory, anticancer, antiinflammatory, chemoprotective, antidiabetic and wound healing potential. This review attempts to describe the ethnobotany, pharmacognosy, traditional uses, chemical constituents, and various pharmacologic activities and other aspects of B. sensitivum.
Keywords: Amentoflavone; angiogenesis; Biophytum sensitivum; seismonasty